Penemuan Hukum dalam Sistem Perkembangan Peradilan di Indonesia - alga hehalatu (Jurnal Hukum Lex Generalis, 2025)
Legal discovery (rechtsvinding) is a fundamental element in the modern legal system, particularly in the context of legal developments in Indonesia, which continue to move in line with social and technological dynamics. Judges not only carry out the function of implementing laws, but also act as interpreters and developers of law when written regulations are inadequate. This article comprehensively discusses the concept of legal discovery, the factors underlying it, the methods of interpretation and construction used by judges and the role of legal discovery in bridging the gap between das sollen and das sein. The discussion is also accompanied by an analysis of court decisions and supporting scientific literature. The research method used is a normative juridical approach by examining primary legal sources such as statutory regulations. Normatively, this study confirms that judges in Indonesia not only play the role of "mouthpiece of the law" (la bouche de la loi) but also as inventors and shapers of law (judge made law) within certain limits. This is in line with the provisions in the Judicial Power Law which requires judges to explore, follow and understand the legal values and sense of justice that exist in society. Legal discovery (rechtsvinding) is an inseparable element of judicial practice in Indonesia, especially in dealing with legal vacuums, unclear norms and the dynamics of societal developments that are not always followed by the formation of laws and regulations. and jurisprudence, as well as secondary legal sources in the form of literature and legal scientific works.